2012
DOI: 10.1111/j.1744-7429.2011.00850.x
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Impacts of Ant and Spider Interactions: Herbivory Reduction in a Tropical Savanna Tree

Abstract: Multiple predators often have effects on their common prey populations that cannot be predicted by summing the effects of each predator at a time. When predators forage on the same vegetation substrate, intraguild interactions might cause emergent outcomes for the plants on which the predators co-occur. We experimentally evaluated the effects of spiders and ants on herbivory and reproduction in the extrafloral nectary-bearing tree Qualea multiflora (Vochysiaceae). Plants were divided in four experimental group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
1
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 51 publications
2
73
1
5
Order By: Relevance
“…Recent evidences have shown that such food resource may be crucial for insect development (Byk & Del-Claro 2011) and is part of the diet of many predatory arthropods like ants (Nascimento & Del-Claro 2010) and spiders (Nahas et al 2012). Since nymphs of A. opsimus may feed more frequently on nectar than on prey, plant derived substances may even be enough for nymph development like Stoner et al (1975) suggested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidences have shown that such food resource may be crucial for insect development (Byk & Del-Claro 2011) and is part of the diet of many predatory arthropods like ants (Nascimento & Del-Claro 2010) and spiders (Nahas et al 2012). Since nymphs of A. opsimus may feed more frequently on nectar than on prey, plant derived substances may even be enough for nymph development like Stoner et al (1975) suggested.…”
Section: Discussionmentioning
confidence: 99%
“…A large group of animals are attracted to EFNs (Koptur 1992), such as spiders (Ruhren & Handel 1999;Nahas et al 2012) and ants (Oliveira & Brandão 1991;Nascimento & Del-Claro 2010) which provide protection to the plant against herbivores. In return, the animals get the nectar which is an important part of nutrition and can enhance growth and reproduction (Byk & Del-Claro 2011).…”
mentioning
confidence: 99%
“…Species vouchers were deposited in both collections. The species were separated into feeding guilds according to the literature of the taxon (Gibbs et al, 2010;Marinoni et al, 2001;Nahas et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, in a few cases ants have even been seen to affect plant defense negatively (Frederickson and Gordon 2007;Mooney 2007;). Conversely, overly aggressive ants may deter beneficial insects such as predators (Torres-Hernandez et al 2000;Nahas et al 2012), parasitoids (Styrsky and Eubanks 2007;), and pollinators (Ness 2006;Hernández-Cumplido et al 2010;Assunção et al 2014). Several studies have shown that pollinators recognize the dangers posed by aggressive ants (Hernández-Cumplido et al 2010, Assunção et al 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, plants that host ants may incur certain ecological costs. Aggressive ants have been known to deter beneficial insects such a pollinators (Ness 2006;Hernández-Cumplido et al 2010;Assunção et al 2014), predators (Torres-Hernandez et al 2000Nahas et al 2012;, and parasitoids (Styrsky and Eubanks 2007;). …”
Section: Observed Higher Pollination Rates Inmentioning
confidence: 99%